Tanaidomorph Tanaidacea (Crustacea: Peracarida) from Mud-Volcano and Seep Sites on the Norwegian Margin - Błażewicz-Paszkowycz, Magdalena; Bamber, Roger N. (Zootaxa, 2011)
Recent sampling of the benthos has been undertaken around the Håkon Mosby Mud Volcano (HMMV) at around 1280 m depth on the Norwegian-Barents-Spitsbergen continental margin and at two seep-sites further south on the Norwegian Margin, the Nyegga seep-site and the Storegga Slide, at about 730 m depth. The collected material included eleven species of tanaidomorph tanaidacean, ten of which (from eight genera) are analyzed herein. Four of these species, one each in the genera Pseudotanais, Cryptocopoides, Obesutanais, and Akanthophoreus, are new to science. Supplementary descriptions are given for two species originally discovered during the 19th century Ingolf expedition, Typhlotanais mixtus and Meromonakantha irregularis. The genus Magotanais is synonymized with Cryptocopoides; the subfamily Akanthophoreinae, Sieg is restricted and raised to family-rank. The evolution of potentially endemic taxa at ventand seep-sites is discussed.